Analisis Efektivitas Penagihan Pajak Dengan Surat Teguran Dan Surat Paksa Dalam Rangka Penerimaan Pajak Pada Masa Pandemi Covid-19 Tahun 2021 (Studi Kasus Pada KPP Pratama Jakarta Menteng Satu) - Afdila Syafira D; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2022)
The COVID-19 pandemic had an impact on the economy in Indonesia from 2020 to 2021. This can be seen from the decline in state treasury from the tax sector. One of the causes was tax collection that was not optimal. This study aims to determine the effectiveness of tax collection with warning letters and distress warrants in maintaining tax revenues during the 2021 Covid-19 pandemic. Effectiveness is assessed based on the percentage of realized payment with warning letters and distress warrants during tax collection. The analytical method used in this study was a qualitative descriptive method in which the effectiveness of tax collection was analyzed and described based on the theory of whether the implementation of tax collection with warning letters and distress warrants during the pandemic has been effective. The results show that tax collection with letters of warning and distress warrants during 2020- 2021 at The Primary Tax Office of Menteng Satu, Jakarta was not effective and had not been maximized in maintaining tax revenues. Based on the data obtained, tax revenues did not reach the target due to the low understanding of taxpayers about tax collection and their lack of awareness to participate in the campaign held by the Primary Tax Office of Menteng Satu, Jakarta.